Travelling through the Subterranean Rivers of Thought with Noé Jitrik: Criticism, Translation and Canon - Giuliano, Facundo (2021)
This essay introduces an interview and a discussion on one of the most important thinkers of Our America, Noé Jitrik, about the relationships woven between heritages of thought and the problems posed by recognition and the canon, at the same time, translation can be found as a journey in itself that presents its ownepistemic, political and historical complexities.